2007
DOI: 10.1182/blood-2007-03-080044
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the SBDS gene in acquired aplastic anemia

Abstract: Shwachman-Diamond syndrome (SDS; OMIM 260400), an inherited bone marrow failure syndrome, is caused by mutations in both alleles of the SBDS gene, which encodes a protein of unknown function. Here we report heterozygosity for the 258 ؉ 2 T>C SBDS gene mutation previously identified in SDS patients in 4 of 91 patients with apparently acquired aplastic anemia (AA) but not in 276 ethnically matched controls (Fisher exact test, P < .004). Affected patients were young and had a poor outcome; they had reduced SBDS e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
45
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 27 publications
2
45
0
3
Order By: Relevance
“…In a study of 91 patients with apparently acquired AA, four were found to be heterozygous for the 258+2 T-C SBDS gene mutation (Calado et al 2007). These patients did not have clinical evidence of pancreatic exocrine failure or other anomalies associated with SDS.…”
Section: Shwachman-diamond Syndromementioning
confidence: 99%
“…In a study of 91 patients with apparently acquired AA, four were found to be heterozygous for the 258+2 T-C SBDS gene mutation (Calado et al 2007). These patients did not have clinical evidence of pancreatic exocrine failure or other anomalies associated with SDS.…”
Section: Shwachman-diamond Syndromementioning
confidence: 99%
“…8 Short telomeres were previously reported in FA, DBA and SDS, using a variety of different cell types, and methods that are less sensitive than flow-FISH (Table 1). [10][11][12][13][14][15][16][17][18][19][20] Most studies indicated that average values for each group of patients were less than the average for age-matched controls. Telomeres are long DNA repeats and a protein complex at chromosome ends that are essential for genome integrity.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed a heterozygous mutation of SBDS, 258+2T>C, in 4 out of 91 patients with apparently acquired AA. 7 In addition, a mutation of SH2D1A causes X-linked lymphoproliferative syndrome which is associated with fatal Epstein-Barr virus (EBV) infection and AA. 8 Given that a small population of patients with primary EBV infection develops AA, SH2D1A is also a candidate for association with AA.…”
mentioning
confidence: 99%